William Golding between Pessimism and Optimism in Lord of the Flies (Journal of the College of Basic Education, 2023)
William Golding's first novel, Lord of the Flies, published in 1954, is still widely considered as his major work. It is one of the most widely-read, widely- admired, and widely- discussed novels in the last fewdecades. Throughout the novel, he shows a consistent struggle betweengood and evil; goes in parallel with his pessimistic view of human natureand his optimistic aspect represented in the characters of Ralph, Piggyand Simon. This thesis makes Lord of the Flies one of those novels whichcan be given several interpretations and be subject to controversial,critical and analytical approaches. Some perceive a bleak picture ofhumanity offered in Lord of the Flies when the symbol of reason andcommon sense is forced into an outlaw existence, and evil is chasing it.While others celebrate the shining hope of Ralph’s rescue and see thesacrifices as a homage good humanity pays for reaching to a more matureand higher state of being. What is so interesting in this novel is Golding'streatment of evil and his raising a subject of so much concern to thetwentieth century people who have witnessed two horrible world wars.Such concerns were becoming the subject of critical controversies inpopular and scholarly publications. The Struggle between Pessimism and Optimism in Lord of the Flies:Of the many great events of the 20th century, the two World Wars played a great and decisive role in forming new attitudes andopinions. William Golding was among the many writers whose lives weretouched by the calamities and horrors of war, which left an unforgettablestamp on his literary career. The horrors of the World War 11 helped himto perceive some kind of innate human evil, like that explored in Lord ofthe Flies. Golding himself stated that "Lord of the Flies takes thesupposed innocent experience of the island- like life in order to test itagainst the experience of Nazism and Second World War." 1 His work inthe navy where he became a lieutenant and was placed in command of arocket launching ship helped him to formulate this new vision abouthuman nature. During that war, Golding learned how brutal people can beto one another, and witnessed all kinds of inhumanity and persecution